2001
DOI: 10.1002/dmrr.236
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycans in experimental models of diabetes: a role for perlecan in diabetes complications

Abstract: Proteoglycans are ubiquitous extracellular proteins that serve a variety of functions throughout the organism. Unlike other glycoproteins, proteoglycans are classified based on the structure of the glycosaminoglycan carbohydrate chains, not the core proteins. Perlecan, a member of the heparan sulfate proteoglycan (HSPG) family, has been implicated in many complications of diabetes. Decreased levels of perlecan have been observed in the kidney and in other organs, both in patients with diabetes and in animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 114 publications
1
47
0
Order By: Relevance
“…Analogously, desulfation triggered by insulin via Sulf2 may induce functional changes in adipocytes. Interestingly, reduced amounts and an altered function of HSPG have been extensively reported in patients with type 2 and also type 1 diabetes [34,35]. The decrease of HSPG and their sulfation in diabetes may be due to a decrease of N-deacetylase [36], possibly induced by a high glucose level [37].…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, desulfation triggered by insulin via Sulf2 may induce functional changes in adipocytes. Interestingly, reduced amounts and an altered function of HSPG have been extensively reported in patients with type 2 and also type 1 diabetes [34,35]. The decrease of HSPG and their sulfation in diabetes may be due to a decrease of N-deacetylase [36], possibly induced by a high glucose level [37].…”
Section: Discussionmentioning
confidence: 99%
“…This could also account for the loss of anionic charge (as a contributor to the onset of albuminuria) reported in conditions such as diabetes, 36 in which both generalized endothelial dysfunction and loss of perlecan in the GBM (perhaps also in glycocalyx) are early features. 36,37 Expression of HS GAG by CiGEnC suggests their potential of regulating interactions with the neighboring cells via the extracellular matrix. The method used to disrupt the glycocalyx using enzymes was based on two specific aims: First, in the case of neuraminidase, to remove the majority of the glycocalyx without disturbing the integrity of the cell monolayer, and, second, with heparinase III and recombinant HPSE-1, to degrade a specific constituent of glycocalyx (HS GAG, implicated in renal pathology).…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic nephropathy, studies have suggested that decreased synthesis of heparan sulphate proteoglycans [27][28][29][30] such as perlecan [31] is the reason for altered barrier function. Perlecan and agrin are the major proteoglycans in the GBM, both carrying heparan sulphate.…”
Section: Introductionmentioning
confidence: 99%